Competence–Confidence Calibration and Risk Profiling Among Preclinical Nursing Students: A Cross-Sectional Study - Rafika Rosyda; Ria Inriyana; Imam Tri Sutrisno (Jurnal Keperawatan Profesional, 2026)
The transition from preclinical learning to clinical practice requires nursing students to possess adequate competence and self-confidence in performing clinical skills. Mismatch between competence and confidence may affect clinical readiness and patient safety. Objective: This study aimed to analyze the relationship between objective clinical competence and self-confidence among preclinical nursing students and evaluate competence-confidence calibration. Methods: A cross-sectional analytic study was conducted among 41 preclinical nursing students using total population sampling. Objective competence was measured using standardized preclinical assessment scores, while self-confidence was assessed using a validated competency-based questionnaire (Cronbach’s alpha = 0.80). Data were analyzed using descriptive statistics, Pearson correlation, simple linear regression, and z-score–based calibration analysis. Results: A significant moderate positive correlation was found between objective competence and self-confidence (r = 0.58; p < 0.001). Objective competence significantly predicted self-confidence (R² = 0.34; p < 0.001). Calibration analysis showed that 36.6% of students were well-calibrated, 34.1% were overconfident, and 29.3% were underconfident. Conclusion: Objective competence was significantly associated with self-confidence among preclinical nursing students, although competence-confidence mismatch remained common. Formative feedback and reflective learning are needed to improve clinical readiness.